Prevalence And Pattern of Tobacco Use in Rural Community of Jaipur, Rajasthan (India): A Cross Sectional Study - Dixit, Anand M; Jain, Pankaj K; Agarwal, Renu; Gupta, Sandip; Shukla, Sushil K; Rani, Vidya (National Journal of Community Medicine, 2015)
Introduction: Tobacco use is one of the important preventable causes of death and a leading public health problem all over the world. Tobacco users who die prematurely deprive their families’ from income, education and health care. Now it is appropriate the policies should be focused to address any gaps and emerging challenges. Our study is focused to find out these challenges and gaps. Methods: It was community based cross sectional, study. Study area was villages that were covered under the rural health training center area of NIMS Medical College Jaipur. Study subject were adults age more than 18 years. Result: Overall prevalence of tobacco consumers in rural area was 37.8%. It was quite higher among males (48.8%) in comparison to females (14.6%). In smokeless tobacco users Gutkha/pan masala was most popular chewable form of tobacco in young generation. Among the subjects 36 % were willing to quit tobacco at some point. A fewer portion of subject (33.2%) knew that smoking can cause cancer, and only 24.8% and 7.5 % knew of effects on respiratory system and cardiovascular system. Conclusion: Prevalence is quite higher. Awareness regarding ill effect on health is poor. False perception of well-being among users is higher. Those who want to quit tobacco are not able to get proper assistance. Poor and illiterate individuals living in rural area are at the maximum risk of using tobacco.